2017
DOI: 10.1055/s-0036-1583942
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Manufacturers of Computed Tomography–Based Computer-Assisted Surgery Systems Do Exist

Abstract: Study DesignLiterature review.ObjectiveSeveral studies have shown that the accuracy of pedicle screw placement significantly improves with use of computed tomography (CT)-based navigation systems. Yet, there has been no systematic review directly comparing accuracy of pedicle screw placement between different CT-based navigation systems. The objective of this study is to review the results presented in the literature and compare CT-based navigation systems relative only to screw placement accuracy.MethodsData … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…A literature review, which included studies that reported a quantitative method for screw accuracy evaluation (2-mm increments), 30% of which used O-arm navigation, found a higher mean accuracy rate for the StealthSystem (Medtronic) than for the VectorVision (Brainlab) navigation system (98.71% vs 95.82%, respectively). 22…”
Section: Screw Accuracymentioning
confidence: 99%
“…A literature review, which included studies that reported a quantitative method for screw accuracy evaluation (2-mm increments), 30% of which used O-arm navigation, found a higher mean accuracy rate for the StealthSystem (Medtronic) than for the VectorVision (Brainlab) navigation system (98.71% vs 95.82%, respectively). 22…”
Section: Screw Accuracymentioning
confidence: 99%
“…Robotic and navigational advancements have improved the accuracy and safety of pedicle screw placement. [1][2][3] Robotassisted (RA) pedicle screw insertion can be performed via an open or a percutaneous approach with similar accuracy. 4,5 Over the last decade, the integration of intraoperative computed tomography (CT) navigational technology has improved the rate of screw malposition by allowing for greater visualization of spinal anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…Several variations in navigation technology exist. Systems may utilise preoperative scans or CT or MRI scans to display the anatomy relative to a reference frame attached to a fixed bony point on the patient, creating a virtual 3D model of the instruments relative to the bone [ 7 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%